Personalized Medicine for Parkinson's Disease New Concepts and Future of Individualized Management - Titova, Nataliya; Chaudhuri, K. Ray (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Personalized medicine for Parkinson's disease is a growing and emerging concept in light of recent recognition that Parkinson's is a syndromic condition affecting multiple neurotransmitter systems, as well as brain and extracranial structures. The clinical expression is, thus, heterogeneous, and presentation age can range from the 30s to the 90s, with PD in older patients being associated with significant neuropathological comorbidity as well, involving not just misfolded alpha synuclein deposition but also amyloid and tau. Traditional and largely guideline-driven "one size fits all" management strategies adopted in clinical practice are, therefore, often inadequate in holistic management of a patient, particularly when aspects of motor and nonmotor symptoms are taken into consideration. In this supplement of JPM, we present a selection of papers which address several possible strands of personalized medicine in PD, ranging from genomic precision medicine to digital "checklists" to ensure delivery of holistic personalized medicine involving nonpharmacological strategies, as well. We are soliciting any papers addressing biomarkers, genetics and pharmacogenetics, treatment or complementary therapies for personalized or individualized treatment for PD.